Glucose utilization of mucuna bracteata sap by saccharomyces cerevisiae in fermentation process - Mohd Noor, Siti Fatimah; Abdul Halim, Norhazimah; Muhamad, Aida; Abdul Rahman, Nurul Hasziatie Anina; Roddi, Adilah; Norazam, Muhammad Nurhisyam (Penerbit UTHM, 2020)
The usage of cover crops has been increase popularity in the agricultural community. A cover crop is a crop planted mainly to manage soil erosion, soil fertility, soil quality, water, weeds, pests, diseases, biodiversity and wildlife in an agro ecosystem. Besides these advantages, cover crops also have disadvantages. Firstly, in order to terminate the crop, the cost that needed was too high. Next, it can also reduce soil moisture, increased risk of plant disease and increased risk of the pest population. Exceeded cover crops also can increase competition between the cash crops in order to get nutrients [1]. In order to overcome this problem, a research was conducted to study about cover crops as a new biomass source to produce something valuable.